2001
DOI: 10.1136/gut.48.1.103
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma in Central Europe: prognostic features and survival

Abstract: Background and aims-We (Gut 2001;48:103-109)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
165
2
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(179 citation statements)
references
References 38 publications
11
165
2
1
Order By: Relevance
“…30 Tumor burden had also been shown to be an important prognostic indicator, but the cutoff used in previous studies has varied from more than 5 cm diameter of the largest nodule to a tumor involving more than 50% of the liver. 31,32 As expected, patients who were eligible for some form of treatment had better survival than those who were too moribund for any treatment. Nevertheless, treatment in general significantly improved survival even after performance status, MELD score, portal vein thrombosis, and tumor size were controlled for.…”
Section: Discussionmentioning
confidence: 84%
“…30 Tumor burden had also been shown to be an important prognostic indicator, but the cutoff used in previous studies has varied from more than 5 cm diameter of the largest nodule to a tumor involving more than 50% of the liver. 31,32 As expected, patients who were eligible for some form of treatment had better survival than those who were too moribund for any treatment. Nevertheless, treatment in general significantly improved survival even after performance status, MELD score, portal vein thrombosis, and tumor size were controlled for.…”
Section: Discussionmentioning
confidence: 84%
“…In previous reports, factors including the size and number of tumor nodules, micro/macrovascular invasion, and high serum AFP levels were associated with hepatocellular carcinoma recurrence after resection 3,12 and liver transplantation. 4 Similar to other investigators, we found that high serum AFP levels were associated with hepatocellular carcinoma recurrence.…”
Section: Discussionmentioning
confidence: 87%
“…6,7 Mutation of p53 has been implicated in the development of cancers of the breast, colon, lung, prostate, bladder, skin, as well as hepatocellular carcinoma. 6,[8][9][10][11][12] The Ki-67 protein is associated with active cell proliferation. It is expressed in all phases of the cell cycle, except G0, with the highest expression seen in G2/M.…”
mentioning
confidence: 99%
“…In one study involving 245 HCC cases, the median survival from the point of diagnosis was only 8 months (6). In another study of 336 patients, survival was as little as 0.7 months for stage III HCC versus 11.5 months for stage I tumors, with a median survival rate of 2.1 months (7).…”
Section: Introductionmentioning
confidence: 99%